Rooms Available? The Rediscovery of the Relevance of Student Housing for Local Housing Markets - Glatter, Jan; Hackenberg, Katharina; Wolff, Manuel (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
Due to the rising number of students and an increasing shortage in housing in many university cities, debates about student housing are starting to gain more attention from politics, the media, the housing industry and science. As a result, the state of knowledge about the structure and development of the local housing market and its impact is rather limited in both theory and practice. Reliable and comprehensive information about the housing market and its evolution are essential for socio-political and housing-related decisions. This paper aims at filling this research gap. After describing factors related to the rising demand in student housing, case studies focusing on student housing and its political significance are presented. Furthermore, this study characterises the development and structure of supply as well as the demand for student housing, and how these factors interrelate with the local housing market. In light of the current discussion about the housing shortages, the consequences of the rental market conditions for students are highlighted. Finally, this paper concludes by providing possible approaches to ensure market transparency
Keywords: Student housing; University cities; Housing market; Interlinking effects; Renter’s market; Landlord’s market; Studentification